2022
DOI: 10.1021/acsenergylett.2c01324
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Electrochemical Fluoride (De)insertion into CsMnFeF6

Abstract: We report on the reversible, electrochemical (de)fluorination of CsMnFeF 6 at room temperature using a liquid electrolyte. CsMnFeF 6 was synthesized via three methods (hydrothermal, ceramic, and mechanochemical), each of which yields products in a defect pyrochlore structure with varying particle sizes and phase purities. After three galvanostatic cycles, approximately one fluoride ion can be reversibly (de)inserted into mechanochemical CsMnFeF 6 for multiple cycles. Ex situ X-ray absorption spectroscopy confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Cycles six and seven are shown in orange and blue, respectively. Reproduced with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Fluorine Chemistry In Rechargeable Fluoride-ion Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Cycles six and seven are shown in orange and blue, respectively. Reproduced with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Fluorine Chemistry In Rechargeable Fluoride-ion Batteriesmentioning
confidence: 99%
“…Likewise, CsMnFeF 6 was investigated as a cathode material for room-temperature FIBs by Jessica and co-workers in 2022 . CsMnFeF 6 in a defect pyrochlore structure with suitable particle size and phase purity was obtained through a mechanochemical method.…”
Section: Fluorine Chemistry In Rechargeable Fluoride-ion Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…32)), therefore, they are the most promising materials at present. However, using these materials faces another problem: most electrolytes, whether solid [33][34][35] or liquid, 6,9,22,[36][37][38][39][40] are at risk of decomposition because their cathodic limits are located almost the same or higher than the RPs of La/LaF 3 and Ce/CeF 3 . This severely limits the number of available electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Christe et al claimed that tetrahydrofuran (THF) can stabilize free fluoride in quaternary ammonium salts, which provides guidance for the development of LE for FIBs . Inspired by the meaningful discovery, Melot and coworkers , used a solution of 1 M tetra- n -butylammonium fluoride (TBAF) in THF as an LE to construct liquid FIBs. They found that the electrodes (CsMnFeF 6 and ReO 3 ) can realize reversible electrochemical (de)­fluorination behavior.…”
Section: Introductionmentioning
confidence: 99%